Risk Analysis of Time and Cost Factors in the Renovation Project at Vimala Hills Residential Area - Vigie Priantika Putra Hutama; Erizal; Satyanto Krido Saptomo; Naufal Rudini (Jurnal Teknik Sipil dan Lingkungan, 2025)
Construction projects always have uncertainties even in small projects, especially in terms of time and cost. This study aims to identify and analyze the dominant risks in home renovation projects in Vimala Hills Bogor and design mitigation strategies. Data collection was carried out by distributing questionnaires to all project implementers. Data analysis used the severity index method to measure frequency and severity combined with biserial point tests and KR-20 to measure the validity and reliability of 15 risk variables with 30 respondents directly involved in the project. The results showed that there were two dominant risks in the high category, namely bad weather conditions (frequency of 80,00%, impact of 77,50%, and risk value of 16) and change of work (frequency of 56,67%, impact of 64,17%, and risk value of 12). Other risks are in the medium to low category. The mitigation strategies implemented include adjusting work schedules based on weather forecasts, protecting work areas, finalizing the design before construction begins, and implementing formal procedures for work changes. After mitigation, the risk value of the two dominant variables dropped to the low category. These findings confirm the importance of implementing risk management even on small scale projects to prevent delays and cost overruns and increase efficiency so that contractors can achieve optimal project goals in the future.